Proceedings of the 4th International Workshop on Software and Performance 2004
DOI: 10.1145/974044.974078
|View full text |Cite
|
Sign up to set email alerts
|

Generating realistic workloads for network intrusion detection systems

Abstract: While the use of network intrusion detection systems (nIDS) is becoming pervasive, evaluating nIDS performance has been found to be challenging. The goal of this study is to determine how to generate realistic workloads for nIDS performance evaluation. We develop a workload model that appears to provide reasonably accurate estimates compared to real workloads. The model attempts to emulate a traffic mix of different applications, reflecting characteristics of each application and the way these interact with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(29 citation statements)
references
References 14 publications
0
29
0
Order By: Relevance
“…Recall that the value of variable h is 3. After executing the foreach loop in Lines 7-9, T = {(5, 1), (6, 1), (7,4), (8, 2)}. Set T is sorted by the second coordinate in descending order, resulting in T = {(7, 4), (8, 2), (5, 1), (6, 1)}.…”
Section: Flexible Head-body Matching Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…Recall that the value of variable h is 3. After executing the foreach loop in Lines 7-9, T = {(5, 1), (6, 1), (7,4), (8, 2)}. Set T is sorted by the second coordinate in descending order, resulting in T = {(7, 4), (8, 2), (5, 1), (6, 1)}.…”
Section: Flexible Head-body Matching Algorithmmentioning
confidence: 99%
“…Set T is sorted by the second coordinate in descending order, resulting in T = {(7, 4), (8, 2), (5, 1), (6, 1)}. The foreach loop in Lines 11-20 initially selects (7,4) and checks to see if all child states of state 7 can be added to the head part. Since HEAD.…”
Section: Flexible Head-body Matching Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Signature matching is a highly computationally intensive process, accounting for about 75% of the total CPU processing time of modern NIDSes [2,7]. This overhead arises from the fact that most of the time, every byte of every packet needs to be processed as part of the string searching algorithm that searches for matches among a large set of strings from all signatures that apply for a particular packet.…”
Section: Introductionmentioning
confidence: 99%
“…Pattern matching is a time-consuming task in an NIDS. Studies have indicated that it consumes up to 70% of the system's execution time (3)(4)(5)(6) . Therefore, the pattern matching performance is crucial to an NIDS.…”
Section: Introductionmentioning
confidence: 99%